Political Discourse Structure on Joe Biden's Acceptance Speech - Ni Luh Putri Rahayu; Ni Wayan Suastini; I Gusti Agung Sri Rwa Jayantini (International Journal of English Learning and Applied Linguistics (IJELAL), 2021)
Politic is a struggle for power to gain attention and persuade the audience. This study attempts to describe the political discourse on Joe Biden’s Speech. The data were taken from Joe Biden’s acceptance speech at the 2020 Democratic National Convention. The analysis of the data was conducted by a descriptive qualitative method. The writers tried to find the structure of political discourse in Joe Biden’s speech. The result of this study shows there are 8 topics found in Joe Biden’s speech, namely (1) Crises, (2) the country that everyone wishes to live, (3) missions of Joe Biden, (4) Joe Biden and Kamala Harris’s life story and family, (5) the campaign and election’s value, (6) Joe Biden’s reason for running as president, (7) Joe Biden’s opinion of his opponent, and (8) Joe Biden’s perspective about America. Each topic consists of some elements of political discourse structures: local semantic, lexicon, syntax, rhetoric, expression structure, and speech act and interaction. Therefore by considering the use of political discourse structure, the speaker able to persuade the audience.